Endoscopy of the gastrointestinal tract in dogs and cats. Issue 4 (2nd April 2015) - Hall, Ed
Abstract : Flexible endoscopy systems are now affordable and available for small animal practice. Endoscopy forms part of the investigation of gastrointestinal (GI) disease, allowing visualisation and biopsy of the GI tract. This article is intended as a guide to the type of endoscope required and how to perform upper and lower GI endoscopy successfully.